Everything the clinician needs to know about evidence-based anticoagulation in pregnancy. (January 2019) - Scheres, Luuk J.J.; Bistervels, Ingrid M.; Middeldorp, Saskia
Abstract: Pregnancy is a hemostatic challenge: women are prone to thromboembolism during their pregnancy and at the same time, especially during delivery, there is substantial risk of bleeding. Pregnant women are often excluded from randomized controlled trials, and high quality evidence regarding optimal anticoagulant management is thus lacking. Anticoagulants are being used in pregnancy for prevention and treatment of various pregnancy complications such as thrombotic events, preeclampsia and pregnancy loss. When anticoagulant therapy is necessary, special attention should be given to both woman and unborn child. In this review, we aim to 1) provide an overview of safe anticoagulant use in pregnancy, 2) discuss treatment goals in pregnancy, and 3) summarize the evidence available to guide decision making for frequently encountered clinical dilemmas in this field.